The beginning of the 21st century: a paradigm shift in the surgical management of renal cell carcinoma in South America - Dall'Oglio,Marcos F. (2010)
PURPOSE: The incidence of renal cell carcinoma (RCC) has been rising by 2.3 to 4.3% every year over the past three decades. Previously, RCC has been known as the internist’s tumor; however, it is now being called the radiologist’s tumor because 2/3 are now detected incidentally on abdominal imaging. We compared patients who were treated toward the end of the 20th century to those treated during the beginning of the 21st century with regard to RCC size and type of surgical treatment. MATERIALS AND METHODS: The study included 226 patients. For analysis of tumor size, we considered a cut point of < 4 cm and > 4 cm. For analysis of type of surgery performed, we considered radical and partial nephrectomy. RESULTS: After the turn of the century, there was a reduction of 1.57 ± 0.48 cm in the size of the RCC that was operated on. Nephron sparing surgeries were performed in 17% of the cases until the year 2000, and 39% of the tumors were < 4 cm. From 2001, 64% of the tumors measured < 4 cm and 42% of the surgeries were performed using nephron sparing techniques. Mean tumor size was 5.95 cm (± 3.58) for the cases diagnosed before year 2000, and cases treated after the beginning of 21st century had a mean tumor size of 4.38 cm (± 3.27). CONCLUSIONS: Compared with the end of the 20th century, at the beginning of the 21st century due to a reduction in tumor size it was possible to increase the number of nephron sparing surgeries.